Ronnie Gilbert : a radical life in song - Gilbert, Ronnie (University of California Press, 2015)
"Ronnie Gilbert has had a long and colorful career as a singer, actor, activist, therapist, and independent woman of her times. She is best known for her time with the Weavers in the 1940s and '50s, but she went on to collaborate with many other musicians--notably Holly Near and Arlo Guthrie--as well as to write and appear on stage in numerous productions, including her own play, Mother Jones. Ronnie Gilbert traverses sixty years of the twentieth century, sharing her take on the folk-music revival, the Cold War blacklist, the 1960s music scene, and primal therapy. Ronnie Gilbert is a unique historical document for readers interested in music, American politics, and the history of the women's movement and the Left."--Provided by publisher